Peranan Korporat Kredibiliti terhadap Niat Gelagat Kepatuhan Zakat Pendapatan Gaji (Jurnal Pembangunan Sosial, 2011)
This study applies the theory of planned behavior by adding corporate credibility in an attempt to predict  compliance intention behaviour towards zakat on employment income. The objective of this study is to determine the relationship between attitude, subjective norm, perceived behavioural control, and corporate credibility with zakah compliance intention on employment income. Data were generated from 250 Muslim individual in public and private organizations. This study uses structural equation technique as measurement model and structural model in measuring attitude, subjective norm, perceived behavioral control, corporate credibility, and intention. The results suggest that TPB revealed a better goodness of fit model. The results also indicated that the original variable of TPB and corporate credibility play important roles in influencing zakat compliance intention. Implication towards theory and policy makers is also discussed.